JURIDIC ANALYSIS OF FISHERY CRIMINAL ACTIONS TO REALIZE THE SOVEREIGNTY OF THE NATION AND THE STATE (Research Study at Batam Marine and Fishery Resources Supervision Base Office) - Setiadi, Kotot; Idham, Idham; Parameshwara, Parameshwara; Fadllan, Fadllan; Erniyanti, Erniyanti; Ramlam, Ramlam (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
In Indonesia, there are many illegal economic problems, but one of the most detrimental to the state is the problem of Illegal, Unregulated, and Unreported Fishing Practices (IUU Fishing) by foreign ships. IUU Fishing is defined as illegal fishing activities, not reported to the authorized fisheries management institution, and fishery activities that have not been regulated in existing regulations. So the role of law enforcement is very important to tackle acts of lawlessness in Indonesian waters. The form of law enforcement is to implement government policies by applying criminal sanctions in the form of fines, confinement, confiscation/confiscation of evidence and sinking foreign ships that steal fish in Indonesian waters. Article 8 of Law no. 45 of 2009 concerning Fisheries states "Everyone is prohibited from catching fish and/or raising fish using chemicals, biological materials, explosives, tools and/or buildings that can harm and/or endanger the sustainability of fish resources and/or the environment in the area. fishery management area of the Republic of Indonesia.” The fact states that the auction with the practice of this fishing mafia can only harm the State of Indonesia because the costs of fishing operations, ship ad hoc fees, mooring ships and feeding the crew during the court process are not commensurate with the auction results that go into the state treasury. The policy regarding the sinking of foreign ships that carry out illegal fishing activities is a significant policy in preventing the occurrence of fishing theft in the marine territory of the Republic of Indonesia. tools and/or buildings that can harm and/or endanger the sustainability of fish resources and/or the environment in the fishery management area of the Republic of Indonesia.” The fact states that the auction with the practice of this fishing mafia can only harm the State of Indonesia because the costs of fishing operations, ship ad hoc fees, mooring ships and feeding the crew during the court process are not commensurate with the auction results that go into the state treasury. The policy regarding the sinking of foreign ships that carry out illegal fishing activities is a significant policy in preventing the occurrence of fishing theft in the marine territory of the Republic of Indonesia. tools and/or buildings that can harm and/or endanger the sustainability of fish resources and/or the environment in the fishery management area of the Republic of Indonesia.” The fact states that the auction with the practice of this fishing mafia can only harm the State of Indonesia because the costs of fishing operations, ship ad hoc fees, mooring ships and feeding the crew during the court process are not commensurate with the auction results that go into the state treasury. The policy regarding the sinking of foreign ships that carry out illegal fishing activities is a significant policy in preventing the occurrence of fishing theft in the marine territory of the Republic of Indonesia. "The fact is that the auction with the practice of this fishing mafia can only harm the Indonesian state because the costs of fishing operations, ship ad hoc fees, mooring ships and feeding the crew during the court process are not commensurate with the auction results that go into the state treasury. The policy regarding the sinking of foreign ships that carry out illegal fishing activities is a significant policy in preventing the occurrence of fishing theft in the marine territory of the Republic of Indonesia. "The fact is that the auction with the practice of this fishing mafia can only harm the Indonesian state because the costs of fishing operations, ship ad hoc fees, mooring ships and feeding the crew during the court process are not commensurate with the auction results that go into the state treasury. The policy regarding the sinking of foreign ships that carry out illegal fishing activities is a significant policy in preventing the occurrence of fishing theft in the marine territory of the Republic of Indonesia.